Предмет: Математика,
автор: serekuka
− 2(m − 2) +7(m − 8) = − 67
Ответы
Автор ответа:
0
−2(m − 2) + 7(m − 8) = −67
-2m + 4 + 7m - 56 = -67
5m - 52 = -67
5m = -67 + 52
5m = -15
m = -15 : 5
m = -3
-2m + 4 + 7m - 56 = -67
5m - 52 = -67
5m = -67 + 52
5m = -15
m = -15 : 5
m = -3
Автор ответа:
0
санька спс
Автор ответа:
0
бро
Автор ответа:
0
− 2(m − 2) +7(m − 8) = − 67
-2m-2•(-2)+7m-7•8=-67
-2m+4+7m-56=-67
(-2+7)m-(56-4)=-67
5m-52=-67
5m-52+52=-67+52
5m=-67+52
5•m=-15
m=-15:5
m=-3
-2m-2•(-2)+7m-7•8=-67
-2m+4+7m-56=-67
(-2+7)m-(56-4)=-67
5m-52=-67
5m-52+52=-67+52
5m=-67+52
5•m=-15
m=-15:5
m=-3
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: dmitriyderyabin23
Предмет: Українська мова,
автор: Аноним
Предмет: Математика,
автор: абдухмед
Предмет: Математика,
автор: 24roman07